(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Infants are at increased risk of morbidity and mortality. So, it is necessary for clinicians to properly place judgement on if an infant requires hospital admission. However, there is a lack of data on which diseases frequently need hospitalization in infancy. Hence the aim of this study was to provide a comprehensive description of infants requiring admissions to healthcare facilities. Materials and methods : This was a cross-sectional study conducted at the outpatient department of a tertiary level hospital. Hundred infants between 1 month to 12 months of age, who were advised for hospitalization following a provisional diagnosis by an expert clinician were enrolled as study subjects. Their details were obtained from caregivers during their visit and the results were analyzed manually. Results : The mean age of infants was 5.4±3.7 months with 2-month-old being the most common age group. The male: female ratio was 1.6:1 while the ratio forurban vs rural settings was 2.2:1. The most common religion was Islam (87%) followed by Hinduism (12%) and then Buddhism (1%). The most common diagnosis of study subjects in descending order of frequency were acute respiratory infection (46%) acute watery diarrhea (34%) burn and scald injury (13%) congenital disorders (10%) and late onset neonatal sepsis (8%). Conclusion : Most common indicators requiring hospital admissions among infants are acute respiratory infection, acute watery diarrhea, burn and scald injury, congenital disorders and late onset neonatal sepsis. Further study needs to be done to look for seasonal variation and variation between neonates and other under-5 age group children. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 3-6